CAR WASH WASTEWATER TREATMENT PLANNING USING BIOFILTER - Irsan, Robby; Soeryamssoeka, SB (Fakultas Teknik Universitas Tanjungpura, 2022)
Users of motorized vehicles in the city of Pontianak are growing rapidly. For some people who are very busy washing motorbikes is a tiring thing and usually, some people take their vehicles to the car wash. During this time, motorcycle washing providers directly dispose of their waste into the environment, which causes pollution and environmental damage. The technology used is a waste treatment system based on natural materials (biofilter). The method used in this activity is an experimental method that is needed to determine the feasibility of a simple biofilter based on physical parameters, color, turbidity, and smell. The filter media used are palm fiber, gravel, activated charcoal, bio ball, filter cotton, coarse fiber, silica sand, and gauze. The plan for making WWTP is planned to use four tubs that have dimensions of 46 cm x 31 cm x 28 cm. One processing tank uses a bio ball which utilizes a sticky medium to reduce organic matter. This tub is modified into three chambers, while the second processing tub uses palm fiber, coarse fiber, silica sand, gauze, and gravel to filter out fine particles. The third treatment tank uses zeolite, activated charcoal, filter cotton, and stone to filter out fine particles, and the fourth tub serves to collect the treatment water before being discharged into the drainage. The results of the WWTP planning at Basecamp DGCI Chapter Pontianak have 3 tubs are used as treatment tanks and 1 tub as a water reservoir before being discharged into the drainage.